Left Hip Pain Caused by Right Hip Osteoarthritis in a Patient With an Incomplete Cervical Spinal Cord Injury: A Case Report. Issue 3 (25th September 2015) - Flis, Alexandra; Duncan, Christopher; Pelt, Christopher; Rosenbluth, Jeffrey; Willick, Stuart
Abstract: A 70‐year‐old woman with a right hemisensory deficit caused by an incomplete cervical spinal cord injury presented with left hip pain. The clinical assessment suggested that her left‐sided hip pain was attributable to severe right hip osteoarthritis. Her left hip pain resolved completely after she underwent a right total hip arthroplasty. This case is presented, along with a review of the literature on spinal and supraspinal neuronal reorganization after spinal cord injury. This case report suggests the occurrence of central sensory reorganization after an incomplete cervical spinal cord injury, which resulted in a patient perceiving right hip pathology in her left hip.